Staging Desire Queer Readings of American Theater History - Marra, Kim; Schanke, Robert (University of Michigan Press, 2002)
Staging Desire gathers critical and biographical essays on notable stage personalities who made their mark before 1969, when the Stonewall riots accelerated the lesbian and gay rights movement in the United States. How they staged their unconventional sexualities greatly influenced the course of their personal and professional lives, and thus the course of American theater history. The book builds on an earlier collection-the well-received Passing Performances, which focused on actors, directors, producers, and agents-by examining playwrights, lyricists, critics, and designers. Shaping theatrical representations from offstage, these practitioners exploited the special opportunities theater offered as a complex and many-layered medium for expression of transgressive desire. Essays cover the careers of major figures Clyde Fitch, Rachel Crothers, Mercedes de Acosta, Djuna Barnes, Cole Porter, Lorenz Hart, George Kelly, William Inge, James "Acorn" Oaks, Adam "Vagabond" Badeau, Eric Bentley, Loie Fuller, Robert Edmond Jones, and Jean Rosenthal. Grounded in research into the history of sexuality, the book engages central problems of terminology and evidence in analyzing sexual practices of the past and the modes of articulation of sexuality in theater, conditioned by American culture's peculiar anxieties about both.